A Case Series of Fixed Drug Combination of Esomeprazole and Levosulpride Associated Akathisia - Parvaiz Alam; Akanksha Shukla; Dinesh Kataria; Bhavuk Garg; Mini Sharma (Archives of Medicine and Health Sciences)
Gastric symptoms are very common and often associated with gastrointestinal (GI) disorders and other systemic disorders. Several drugs such as esomeprazole and levosulpiride are often used in the management of these symptoms. However, there are reports suggesting an association between specific GI drug combination and the development of akathisia with them. These case series aim to investigate and document the cases of the fixed drug combination of esomeprazole- and levosulpiride-associated akathisia, highlighting this potential adverse effect. This combination is rarely reported to cause akathisia in the literature. Whenever this combination is prescribed, patients and their caregivers should be warned of symptoms of akathisia.